Location-dependent patient outcome and recurrence patterns in IDH1-wildtype glioblastoma - Jungk, Christine; Warta, Rolf; Mock, Andreas; Friauf, Sara; Capper, David; Abdollahi, Amir; Debus, Jürgen; Bendszus, Martin; Deimling, Andreas von; Unterberg, Andreas; Herold-Mende, Christel (Cancers, 2019)
Recent studies suggest that glioblastomas (GBMs) contacting the subventricular zone (SVZ) as the main adult neurogenic niche confer a dismal prognosis but disregard the unique molecular and prognostic phenotype associated with isocitrate dehydrogenase 1 (IDH1) mutations. We therefore examined location-dependent prognostic factors, growth, and recurrence patterns in a consecutive cohort of 285 IDH1-wildtype GBMs. Based on pre-operative contrast-enhanced MRI, patients were allotted to four location-dependent groups with (SVZ+; groups I, II) and without (SVZ−; groups III, IV) SVZ involvement or with (cortex+; groups I, III) and without (cortex−; groups II, IV) cortical involvement and compared for demographic, treatment, imaging, and survival data at first diagnosis and recurrence. SVZ involvement was associated with lower Karnofsky performance score (p < 0.001), lower frequency of complete resections at first diagnosis (p < 0.0001), and lower non-surgical treatment intensity at recurrence (p < 0.001). Multivariate survival analysis employing a Cox proportional hazards model identified SVZ involvement as an independent prognosticator of inferior overall survival (p < 0.001) and survival after relapse (p = 0.041). In contrast, multifocal growth at first diagnosis (p = 0.031) and recurrence (p < 0.001), as well as distant recurrences (p < 0.0001), was more frequent in cortex+ GBMs. These findings offer the prospect for location-tailored prognostication and treatment based on factors assessable on pre-operative MRI.